Automated Finishing with Autofinish - Gordon, David; Desmarais, Cindy; Green, Phil

(untitled) (Genome Research, 2001)
Currently, the genome sequencing community is producing shotgun sequence data at a very high rate, but finishing (collecting additional directed sequence data to close gaps and improve the quality of the data) is not matching that rate. One reason for the difference is that shotgun sequencing is highly automated but finishing is not: Most finishing decisions, such as which directed reads to obtain and which specialized sequencing techniques to use, are made by people. If finishing rates are to increase to match shotgun sequencing rates, most finishing decisions also must be automated. The Autofinishcomputer program (which is part of the Consed computer software package) does this by automatically choosing finishing reads.Autofinish is able to suggest most finishing reads required for completion of each sequencing project, greatly reducing the amount of human attention needed. Autofinish sometimes completely finishes the project, with no human decisions required. It cannot solve the most complex problems, so we recommend thatAutofinish be allowed to suggest reads for the first three rounds of finishing, and if the project still is not finished completely, a human finisher complete the work. We compared thisAutofinish-Hybrid method of finishing against a human finisher in five different projects with a variety of shotgun depths by finishing each project twice—once with each method. This comparison shows that the Autofinish-Hybrid method saves many hours over a human finisher alone, while using roughly the same number and type of reads and closing gaps at roughly the same rate.Autofinish currently is in production use at several large sequencing centers. It is designed to be adaptable to the finishing strategy of the lab—it can finish using some or all of the following: resequencing reads, reverses, custom primer walks on either subclone templates or whole clone templates, PCR, or minilibraries.Autofinish has been used for finishing cDNA, genomic clones, and whole bacterial genomes (see http://www.phrap.org).